Humankind’s Two Bags: Between the Aesopian tradition and Phaedrus - Anjos, Sara; Guimarães Tavares da Silva, Rafael (Revista Archai, 2025)
The fable genre in Greco-Roman culture has popular and oral roots, establishing curious dialogues with poetic and philosophical traditions throughout its history. Our article addresses two fables that share certain elements of a story of human creation: the first, written in Greek and attributed to Aesop, is entitled “Two Bags” [Πῆραι δύο]; the other, composed in Latin by Phaedrus, is entitled “On the Vices of Humans” [De Vitiis Hominum]. We advance on philological bases to contextualize in historical terms each of these texts, in order to understand the interplay of meaning established by them, especially with the Cynic tradition (in the first case) and with the Roman political context (in the second). To this end, we undertake a careful reading of intertextual and reception issues.